2006
DOI: 10.2337/db06-0244
|View full text |Cite
|
Sign up to set email alerts
|

STAT5 Activity in Pancreatic β-Cells Influences the Severity of Diabetes in Animal Models of Type 1 and 2 Diabetes

Abstract: Pancreatic ␤-cell growth and survival and insulin production are stimulated by growth hormone and prolactin through activation of the transcription factor signal transducer and activator of transcription (STAT)5. To assess the role of STAT5 activity in ␤-cells in vivo, we generated transgenic mice that expressed a dominant-negative mutant of STAT5a (DNSTAT5) or constitutive active mutant of STAT5b (CASTAT5) under control of the rat insulin 1 promoter (RIP). When subjected to a high-fat diet, RIP-DNSTAT5 mice s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 54 publications
(48 reference statements)
6
35
0
1
Order By: Relevance
“…By activating the JAK/STAT pathway, GH can also stimulate β-cell survival. The JAK/STAT-activated suppressors of cytokine signaling block damage triggered by cytokines such as IFN-γ or TNF-α (45), and expression of a constitutively active form of STAT5b has a protective effect on β-cells in a model of streptozotocin-induced diabetes (46). NOD-Tg bGH mice showed periinsulitis, although we found no sign of degradation of the periinsular laminin layer, and no antiinsulin antibodies in serum.…”
Section: Discussionmentioning
confidence: 46%
“…By activating the JAK/STAT pathway, GH can also stimulate β-cell survival. The JAK/STAT-activated suppressors of cytokine signaling block damage triggered by cytokines such as IFN-γ or TNF-α (45), and expression of a constitutively active form of STAT5b has a protective effect on β-cells in a model of streptozotocin-induced diabetes (46). NOD-Tg bGH mice showed periinsulitis, although we found no sign of degradation of the periinsular laminin layer, and no antiinsulin antibodies in serum.…”
Section: Discussionmentioning
confidence: 46%
“…The role of the STAT5 pathway in the beta cell has been examined in vivo using two separate approaches. RIP-DNStat5 transgenic mice [38] and mice with Cre-lox elimination of Stat5 in the beta cell and pancreas [39] display no major alterations in islet development or function under basal conditions. However, the loss of STAT5 signalling in RIP-DNStat5 mice had a negative impact in the setting of type 1 and 2 diabetes [38] and a mild effect on glucose tolerance with age in the pancreasspecific knockout mice [39], suggesting the requirement of this signalling pathway at least under stress-induced conditions in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is probably mediated by increased expression of Bcl-xL. Studies in transgenic mice expressing STAT5 mutants in the beta cells confirmed the protective effect of STAT5 against high fat diet induced diabetes and multiple low dose streptozotocin induced diabetes (Jackerott et al, 2006). The role of GH regulated calcium metabolism in beta cell is discussed in another paper in this issue (Zhang et al, 2008) and the role of STAT5 in beta cells was recently reviewed (Dalgaard et al, 2008).…”
Section: Signalling Pathways Involved In Cyclin D Expressionmentioning
confidence: 97%